2018
DOI: 10.24953/turkjped.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of out-of-hospital cardiopulmonary arrest in children: A multicenter cohort study

Abstract: The aim of this study was to evaluate the demographic characteristics of children who experienced out-of-hospital cardiopulmonary arrest (CPA), and to assess the impact of the bystander cardiopulmonary resuscitation (CPR) on the survival rate of witnessed arrests and the effects of the arrest and CPR durations on the neurological outcomes. This multicenter, retrospective study included a total of 182 patients who underwent CPR for out-of-hospital CPA between January 2008 and December 2012 at six centers in Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A meta-analysis of 67 studies including subjects in all age groups found the survival rate to be lowest in Asia at 2% while it was 6% in North America, 9% in Europe, and 11% in Australia (13). The out-of-hospital cardiac arrest survival rate was 14.3% and a shockable rhythm was detected in only 4 of 182 patients at the time of diagnosis in a study conducted in the pediatric age group in our country (14). Low survival rates can be explained by the lack of training and awareness of non-hospital staff and the difficulty of accessing AED devices.…”
Section: Methodsmentioning
confidence: 68%
“…A meta-analysis of 67 studies including subjects in all age groups found the survival rate to be lowest in Asia at 2% while it was 6% in North America, 9% in Europe, and 11% in Australia (13). The out-of-hospital cardiac arrest survival rate was 14.3% and a shockable rhythm was detected in only 4 of 182 patients at the time of diagnosis in a study conducted in the pediatric age group in our country (14). Low survival rates can be explained by the lack of training and awareness of non-hospital staff and the difficulty of accessing AED devices.…”
Section: Methodsmentioning
confidence: 68%
“…Each year 7037 children experience out-of-hospital cardiopulmonary arrest with a survival rate of 6.4%. [ 1 2 ] The most common causes of cardiopulmonary arrest in childhood are sudden infant death syndrome, trauma, and pulmonary diseases. [ 3 ] The younger the child, the higher his or her permanent neurological complications and mortality rate after cardiopulmonary arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac arrest in pediatric groups is rare and most commonly due to respiratory arrest, as opposed to adult groups, when cardiac problems are more common [12]. The prognosis of in-hospital or out-of-hospital cardiopulmonary resuscitation (CPR) in pediatric groups is poor and may result in a devastating neurological deficit in the surviving patients [13,14]. According to the American Heart Association, if the heart stops beating, the first step in saving a life is to perform basic life support (BLS), starting with CPR.…”
Section: Introductionmentioning
confidence: 99%
“…To provide high-quality CPR, the provider should be well trained and understand the significance of time consumed performing CPR [14]. In order to rescue the patient's life, alleviate the pain, terminate the progression of an injury, and obtain a favorable neurological outcome, correct CPR must be administered [14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation